If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(t + 1) = 14 Reorder the terms: -7(1 + t) = 14 (1 * -7 + t * -7) = 14 (-7 + -7t) = 14 Solving -7 + -7t = 14 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -7t = 14 + 7 Combine like terms: -7 + 7 = 0 0 + -7t = 14 + 7 -7t = 14 + 7 Combine like terms: 14 + 7 = 21 -7t = 21 Divide each side by '-7'. t = -3 Simplifying t = -3
| -7(t+1)=4 | | 1/2(18x+2)=3(3x-2)-3(x-7) | | 1/2(p+6)=7/2(3-p) | | 3x^2+(k-1)x-2=0 | | 27-19=4(x-6) | | -7x+1=9 | | 30+5y-12=17y-9-3y | | x+23+4x=-22-4x-27 | | -x(x-2)(x+2)(x+2)=0 | | b^12*b^10= | | -0.4x^2+2.2x+4.7=0 | | w^6*w^8= | | 5q^2-2bq-3=0 | | -4x+1=33 | | 2m/5+4=-10/9-3 | | P(2)-10P+22=0 | | 3(z-4)+6= | | -11/7=z-2/3 | | 2log(x-3)-log(x+1)=2 | | k*k^12= | | 4x^2+7x=6 | | a^4-6a^2+5=0 | | 6+2(1+2x)=29-3x | | 2x-7(3-2x)=11 | | 2((1.5+2)+(1.5+3))=16 | | 154=4x^2+26x+40 | | -4+4x=-8 | | 2((x+2)+(x+3))=16 | | n+6=19 | | y=3x-1-4 | | (u+3)(2u-1)=-3 | | 8(4-6)=4(8x+7) |